KNOWLEDGE OF MODERN TEETH WHITENING METHODS: "ZOOM-4" AND "BEYOND POLUS" - Ochilov Hayotjon; Axmedov Alisher Astanovich (European International Journal of Multidisciplinary Research and Management Studies, 2024)
This article describes the methods of chemical bleaching and contraindications to bleaching.